Decentralization as a global phenomenon in the reform of governance structure - Gałuszka, Jolanta (Decentralizacja jako globalny fenomen w reformie zarządzania finansami publicznymi, 2011)
The article presents the problem of decentralization in the public sector in the context of good governance and proper architecture of the fiscal policy. We can observe discussion that has attracted attention to the growing gap between the tax systems that the policymakers of some countries might wish to have and those that global forces are forcing them to adopt. In the last decade many economies in the world have experienced currency, debt, financial and banking crises and most of the public finance had to be able to bear it by creating policy framework for reducing the moral hazard risks
Nauki o Finansach = Financial Sciences, 2011, Nr 1 (6), s. 79-91
Keywords: decentralization; fiscal decentralization; fiscal policy; governance; motivation